The role of lncRNA-mediated ceRNA regulatory networks in liver fibrosis - Jianhao Jiang; Ilgiz Gareev; Tatiana Ilyasova; Alina Shumadalova; Weijie Du; Baofeng Yang (Non-coding RNA Research, 2024)
In the dynamic realm of molecular biology and biomedical research, the significance of long non-coding RNAs (lncRNAs) acting as competing endogenous RNAs (ceRNAs) continues to grow, encompassing a broad spectrum of both physiological and pathological conditions. Particularly noteworthy is their pivotal role in the intricate series of events leading to the development of hepatic fibrosis, where hepatic stellate cells (HSCs) play a central role. Recent strides in scientific exploration have unveiled the intricate involvement of lncRNAs as ceRNAs in orchestrating the activation of HSCs. This not only deepens our comprehension of the functioning of proteins, DNA, and the extensive array of coding and noncoding RNAs but also sheds light on the intricate molecular interactions among these molecules. Furthermore, the well-established ceRNA networks, involving classical interactions between lncRNAs, microRNAs (miRNAs), and messenger RNAs (mRNAs), are not mere bystanders; they actively participate in instigating and advancing liver fibrosis. This underscores the pressing need for additional thorough research to fully grasp the potential of ceRNA. The unyielding pursuit of knowledge in this field remains a potent driving force with the capacity to enhance the quality of life for numerous individuals grappling with such diseases. It holds the promise of ushering in a new era of precision medicine, signifying a relentless dedication to unraveling the intricacies of molecular interactions that could pave the way for transformative advancements in the diagnosis and treatment of hepatic fibrosis.